Factor associated with self-reported work-related musculoskeletal disorders in Brazilian adults - Ada Ávila Assunção; Mery Natali Silva Abreu
ABSTRACT OBJECTIVE To describe the prevalence of work-related musculoskeletal disorder (WMSD) and analyze the factors associated with this outcome in the Brazilian population. METHODS In this cross-sectional, population-based study, we use data from the National Survey on Health (PNS) of 2013. The sample was composed of 60,202 Brazilians aged 18 years or older. The outcome variable was the occurrence of self-reported WMSD. Sociodemographic and occupational characteristics, personal resources, and health conditions were investigated as explanatory variables. Analyses were performed with the software Stata 12.0 and considered the weighting imposed by the sampling design of the study. Then, univariate and multivariate binary logistic models were carried out, considering a significance level of 5%. RESULTS The results obtained indicated that the prevalence of WMSD in the Brazilian population was of 2.5%, ranging from 0.2% (Acre) to 4.2% (Santa Catarina). The factors associated with a greater chance of occurrence of WMSD were: female sex (OR = 2.33; 95%CI 1.72-3.15); be temporarily away from work (OR = 2.44; 95%CI 1.41-4.23); be exposed to noise at the workplace (OR = 2.16; 95%CI 1.68-2.77); seniority equal to or greater than 4.5 years at the current job (OR = 1.37; 95%CI 1.09-1.72); participate in volunteer work (OR = 1.65; 95%CI 1.25-2.17); report medical diagnosis of arthritis or rheumatism (OR = 2.40; 95%CI 1.68-3.44); and depression (OR = 2.48; 95%CI 1.86-3.31). On the other hand, factors associated with less chance of WMSD were: not having a partner (OR = 0.73; 95%CI 0.37-0.71) and working in an open environment (OR = 0.51; 95%CI 0.37-0.71). CONCLUSIONS The associated factors and the prevalence found indicate regional and gender differences. Special attention to comorbidities and environmental noise monitoring would benefit the health of workers in the Country.